The potential of TPACK-based biology learning to improve students' habits of mind - Bariroh, Ghurrotul; Surtikanti, Hertien Koosbandiah (Jurnal Mangifera Edu, 2024)
The significance of habits of mind in achieving student success was contrasted with the low level of students' habits of mind in biology learning. TPACK is a 21st-century learning approach that has the potential to improve students' habits of mind. However, this was not followed by biology teachers' mastery of TPACK, which was relatively low. So far, there has been no research that examines the role of TPACK on students' habits of mind in biology learning. This paper aims to find out the potential and implementation of TPACK-based biology learning in improving students' habits of mind. The method used was a Systematic literature review with 20 sample international and national articles. Access to digital resources enriches students' ideas and supports the development of critical thinking, creativity, and self-regulation skills. In this way, teachers are expected to not only increase their knowledge of content and pedagogy but also integrate technology into learning, allowing students to gain more meaningful knowledge. The form of implementing this technology integration can be in the form of learning media or learning assessments. What was found in this writing is that students' habits of mind can be formed through classroom learning, one of which is the TPACK approach. Recommendations for choosing more diverse biological material were also proposed in this paper so that learning becomes more dynamic, contextual, and then students' habits of mind are achieved.